Improving Understanding of Islamic Religious Education Materials through an Active Learning Approach in Class XI of SMAN 1 Kepenuhan in the 2024/2025 Academic Year - Walad, Khairul (STKIP Rokania Pasir Pangaraian, 2024)
This study aims to improve the understanding of Islamic Religious Education (PAI) material in class XI students of SMAN 1 Kepenuhan through the application of an active approach in learning. The active approach was chosen in the hope of increasing students' involvement in the learning process and facilitating a deeper understanding of the material. This study used the classroom action research (PTK) method implemented in two cycles, each consisting of planning, implementation, observation, and reflection. The results showed that the implementation of an active approach succeeded in improving students' understanding of PAI materials. Based on observation results, there was a significant increase in student participation, involvement in group discussions, and acceptance of learning materials. In addition, test data showed an increase in students' average test scores from 70 in cycle I to 84 in cycle II. This increase shows the effectiveness of the active approach in improving the understanding of Islamic Religious Education materials. Overall, this study contributes to the development of more interactive and effective learning methods in the context of Islamic Religious Education at SMAN 1 Kepenuhan, as well as providing recommendations for Islamic Education teachers to adopt active approaches in the learning process.